PLACE AND ROLE OF THE COURSE «FUNDAMENTALS OF TRAUMA PSYCHOLOGY» IN THE TRAINING OF SOCIAL WORKERS - Радченко, М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article defines the role and place of the discipline "The basics of trauma psychology" in the training of social workers. The special role of the social worker in the current conditions of increasing number of psycho-traumatic situations is emphasized. The content of the concept of "psychological trauma" is investigated on the basis of the scientific literature analysis, and the history of the term "post-traumatic stress disorder" (PTSD) is traced. The specifics of the work of the social worker in the process of assisting psycho-traumatized people are determined and the relevance of teaching this course to future social workers is substantiated. Listed are the methods of research proposed by the author of the article tasks. Information is provided about one of the sources of this discipline - a training course in trauma psychology. conducted by Canadian researcher Daria Shevchuk. The thematic plan of the course “The basics of trauma psychology” and “Letter of self-control” is offered, the use of which is aimed at improving the self-regulation skills of future specialists. The results of the questionnaire of students are given: they determine their expectations from the study of the course, the most useful and interesting topics, the skills to be formed, the principles of presentation of educational material, the ratio of practical and theoretical parts of the course, as well as the attitude of students to the assessment system implemented by the course author. the content of the program "sign savings". The following is an example of a "Letter of self-control and typical statements of students who participated in the survey. The stages of work with children and adults who have been affected by psycho-traumatic factors are proposed. The specifics of the proposed discipline, the basic requirements for teaching teaching material are determined. The prospects for further research in this direction, which are to deepen the practical component of this course, are outlined